Análisis financiero, instrumento para la toma de decisiones financiera. Caso de estudio: Ginafruit S.A. - Rodríguez Seminario, Lizzeth Carolay; Herrera Medina, Rosa Jhulissa (Universidad Técnica de Machala, 2022)
One of the main responsibilities of the manager of a company is to make decisions that are decisive for the achievement of the goals and objectives set. The analysis of financial statements is a set of tools that are used to know the situation of the company in order to make economic and financial decisions. The main objective of this case analysis is to relate financial analysis as an instrument for making financial decisions in GINAFRUIT S.A. for the periods 2019 - 2020. Its scope focuses on analyzing the relationship between financial indicators and financial decision making and determining its importance as an application tool by company management. The methodology used for the elaboration of the work contains a quantitative approach, accompanied by a positivist paradigm, which is based on the deductive method, with an analytical investigation, of transactional design, using the closed survey technique and using the survey questionnaire as an instrument, applied to the accounting assistant, financial manager and accountant of the banana sector company in the study context. In the results after having applied the survey and the financial analysis to the basic financial statements, the level of liquidity, solvency, indebtedness and profitability that the company possesses was known, reflecting the company in a non-optimal economic and financially adequate level., as well as showed that the company does not have a due financial decision-making process and does not use financial analysis as a step to follow before making the financial decision. It is concluded that the application of financial analysis in GINAFRUIT S.A has a positive impact, influencing financial decision-making, allowing administrators to keep adequate control of their economic and financial resources.
Una de las primordiales responsabilidades del gerente de una empresa es tomar decisiones que sean determinantes para el logro de las metas y objetivos trazados. El análisis de los estados financieros es un conjunto de herramientas que son utilizadas para conocer la situación de la empresa con la finalidad de tomar decisiones económicas y financieras. El presente análisis de casos tiene como objetivo principal relacionar el análisis financiero como instrumento para la toma de decisiones financieras en GINAFRUIT S.A. por los periodos 2019 - 2020. Su alcance se centra en analizar la relación entre indicadores financieros y la toma de decisiones financieras y determinar su importancia como herramienta de aplicación por parte de la gerencia de la empresa. La metodología empleada para la elaboración del trabajo contiene un enfoque cuantitativo, acompañado con un paradigma positivista, que se basa en el método deductivo, con una investigación analítica, de diseño transaccional, empleando la técnica de encuesta cerrada y utilizando como instrumento el cuestionario de encuestas, aplicada a la asistente contable, jefe financiero y contador de la empresa de sector bananero del contexto de estudio. En los resultados luego de haber aplicado la encuesta y el análisis financiero a los estados financieros básicos, se conoció el nivel de liquidez, de solvencia, endeudamiento y rentabilidad que posee la empresa que reflejan a la empresa en un nivel no óptimo económico y financieramente adecuado, así como también mostró que la empresa no cuenta con un debido proceso de toma de decisiones financieras y no emplean el análisis financiero como un paso a seguir antes de tomar la decisión financiera. Se concluye que la aplicación del análisis financiero en GINAFRUIT S.A impacta de manera positiva, influyendo en la toma de decisiones financieras, permitiéndoles a los administradores, llevar un control adecuado de sus recursos económicos y financieros.
Keywords: ANALISIS FINANCIERO; TOMA DE DECISIONES; INDICADORES